Effects of aerobic exercise training on the heart rate-work rate relationship and estimation of anaerobic threshold in obese females - Özçelik, O?uz; Keleştimur, Haluk (My University, 2006)
Aim: The purpose of this study was to assess the effects of aerobic training on the relationship between the heart rate deflection point and anaerobic threshold (AT). Patients and Methods: Seventeen untrained, obese subjects (body mass index: 39.5 ± 1.2 kg/m2) completed 2 incremental ramp exercise tests (15 W/min) up to the point of exhaustion using an electromagnetically-braked cycle ergometer; once at the onset and once at the end of a 4-week period. All subjects participated in a regular anaerobic exercise training programme (45 min, 3 times per-week, for 4 weeks) combined with a hypocaloric diet. Heart rate was recorded with a polar monitor. AT was estimated using the ventilation-metabolism relationship, but was determined from capillary blood lactate samples. Results: Of all the subjects, only 4 (23.5%) had a heart rate deflection during pre-training, while 3 (17.6%) did during post-training conditions. Additionally, the heart rate deflection point overestimated (20.6%) the AT: 90.0 ± 7.2 W vs. 75.7 ± 6.5 W (P = 0.01). After training, the heart rate-work rate relationship changed in 7 subjects. Conclusion: These data indicated that a deflection point in heart rate does not often occur, and, when it does, it does not coincide with AT, either in pre-training or post-training conditions. © TÜBİTAK.
Keywords: Anaerobic threshold; Exercise test; Heart rate deflection point; Obesity